2001
DOI: 10.1260/0957456011498687
|View full text |Cite
|
Sign up to set email alerts
|

Global Control of Vibration Using a Tunable Vibration Neutraliser

Abstract: Tunable vibration neutralisers are currently used to control harmonic vibration of structures at the point at which they are attached, and the way in which the characteristics of the neutralisers influence their effectiveness in this role are reasonably well understood. However, the use of tunable vibration neutralisers to control global vibration of a structure has not been so well explored, and in this article the neutraliser parameters that influence the vibrational kinetic energy of a host structure are hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…(Brennan, 1997) defines the attenuation D provided by a TVN for harmonic excitation as the ratio of the vibration amplitude at A without the TVN to the amplitude there with the TVN attached and optimally tuned:…”
Section: Tuned Vibration Neutralisermentioning
confidence: 99%
See 4 more Smart Citations
“…(Brennan, 1997) defines the attenuation D provided by a TVN for harmonic excitation as the ratio of the vibration amplitude at A without the TVN to the amplitude there with the TVN attached and optimally tuned:…”
Section: Tuned Vibration Neutralisermentioning
confidence: 99%
“…Also, for given absorber damping, the TVA's attenuating capability degrades as , ae ff m is reduced. In fact, for a host structure that is a rigid machine of mass M mounted on soft isolators, (Brennan , 1997) showed that…”
Section: Tuned Vibration Neutralisermentioning
confidence: 99%
See 3 more Smart Citations